Speaking Anxiety in English Learning in Grade XI Students of Walisongo Pecangaan High School: Forms, Factors, and Strategies to Overcome It - Sulaiman, Raehani; Candraloka, Olyvia Revalita (Linguistics and ELT Journal, 2025)
This study maps the forms, factors, and strategies for overcoming speech anxiety in grade XI students at Walisongo Pecangaan High School (pesantren context). Using a descriptive qualitative approach (case study), six students were selected on a purposive–maximum variation basis. Data were collected through semi-structured interviews and class observations in speaking sessions, then analyzed thematically by triangulating cognitive, physiological, and behavioral indicators. The results showed that the majority of the speakers were at medium to high levels. Four forms of anxiety arise and intertwine: (1) physiological—cold sweats, tension, speech blocking; (2) cognitive—a sense of "inadequacy", a concern about grammar accuracy; (3) behavior—avoidance, hesitation to start, waiting to be called; (4) linguistics—vocabulary limitations, accuracy focus. Internal factors are mainly low self-efficacy and accuracy orientation; External factors include a class climate that is too quiet/serious and peer judgment. Teacher support—wait-time, prompting, and non-judgmental feedback—acts as a damper that lowers affective filters and maintains willingness to communicate. Practical implications include tiered scaffolding (pairs→small groups→plenary), pre-task planning with keyword cards, delayed feedback policies, and fun strategies such as TPR-storytelling. This study enriches the study of FLCA in the context of pesantren and recommends mixed research with FLCAS adaptation, WTC/performance measurement, quasi-experimental test of intervention packages, and longitudinal tracking (XI→XII).